Validity of the International HIV Dementia Scale in Brazil Validade da Escala Internacional de Demência pelo HIV no Brasil - Roiza Almeida Rodrigues; Raquel Lisboa Oliveira; Beatriz Grinsztejn; Marcus Tulius T. Silva (Arquivos de Neuro-Psiquiatria)
HIV-associated neurocognitive disorders (HAND) remain prevalent in highly active antiretroviral therapy (HAART) era. Tests to detect HAND are needed for early diagnosis and treatment. Validity of International HIV Dementia Scale (IHDS) has been determined in different countries. The aims of this study were validate IHDS in a Brazilian cohort of HIV-patients and verify if IHDS can be reliably administered by a non-clinician health professional. One hundred and eighty-seven (187) patients were submitted to a full neuropsychological assessment. IHDS was administered twice to each patient (by a non-clinician and by a neurologist). HAND was diagnosed in 98 individuals (68 on HAART). IHDS had sensitivity of 55% and specificity of 80%. IHDS had fair agreement with neuropsychological tests (k 0.355) and moderate-to-strong agreement between different evaluators (interclass correlation coefficient (ICC) 0.684). HAND is prevalent nowadays. IHDS is quick and easy to administer, but has marginal sensitivity for the detection of HIV cognitive impairment other than dementia. Distúrbios neurocognitivos associados ao HIV (HAND) ainda são comuns em pacientes usando terapia antirretroviral de alta eficácia (HAART). Testes diagnósticos para detecção de HAND são necessários para diagnóstico e terapia precoces. Nossos objetivos foram validar em uma população brasileira a escala internacional de demência pelo HIV (IHDS), já utilizada em outros países, e avaliar se pode ser confiavelmente aplicada por um profissional não médico. Avaliamos 187 pacientes com uma extensa bateria neuropsicológica. IHDS foi ministrada duas vezes (por médico e não médico). HAND foi diagnosticada em 98 indivíduos (68 em uso de HAART). A IHDS teve sensibilidade de 55% e especificidade de 80%, com pouca concordância com os testes neuropsicológicos (k 0,355) e moderada a forte concordância entre observadores (coeficiente de correlação interclasse (ICC) 0,684). HAND ainda é prevalente nos dias atuais. IHDS é um instrumento rápido e fácil de ser aplicado, mas com baixa sensibilidade para detecção de déficit cognitivo outro que não demência.